2013
DOI: 10.1097/ogx.0b013e3182877729
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Added to Neoadjuvant Chemotherapy for Breast Cancer

Abstract: Background-Bevacizumab and the antimetabolites capecitabine and gemcitabine have been shown to improve outcomes when added to taxanes in patients with metastatic breast cancer. The primary aims of this trial were to determine whether the addition of capecitabine or gemcitabine to neoadjuvant chemotherapy with docetaxel, followed by doxorubicin plus cyclophosphamide, would increase the rates of pathological complete response in the breast in women with operable, human epidermal growth factor receptor 2 (HER2)-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 23 publications
3
52
0
4
Order By: Relevance
“…More patients achieved pCR in the combination-therapy arm compared to the chemotherapy alone arm, in line with reports from previous studies (6,7,10,11). A significant benefit of adding bevacizumab was observed in the ER-positive subgroup consistent with the larger NSAPB-B40 trial (11), in contradiction to the GeparQuinto trial, where the ERnegative tumors were found to benefit from bevacizumab (10), and the CALGB40603 study, including patients with a low ER expression, or triple negative tumors (6). The clinical toxicity increased with bevacizumab treatment, as more patients experienced febrile neutropenia in addition to hypertension and episodes of bleeding.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…More patients achieved pCR in the combination-therapy arm compared to the chemotherapy alone arm, in line with reports from previous studies (6,7,10,11). A significant benefit of adding bevacizumab was observed in the ER-positive subgroup consistent with the larger NSAPB-B40 trial (11), in contradiction to the GeparQuinto trial, where the ERnegative tumors were found to benefit from bevacizumab (10), and the CALGB40603 study, including patients with a low ER expression, or triple negative tumors (6). The clinical toxicity increased with bevacizumab treatment, as more patients experienced febrile neutropenia in addition to hypertension and episodes of bleeding.…”
Section: Discussionsupporting
confidence: 80%
“…Increases in febrile neutropenia and hypertension have also been seen in similar studies (10,11). The clinical practice guidelines at the time of the study were not recommending the use of G-CSF for all patients, only those having experienced febrile neutropenia, and this may have increased the frequency of this adverse event.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…G-CSF support was used in 93 % of chemotherapy cycles resulting in low rates of neutropenia (3 %). In contrast, the NSABP-B40 trial [26] reported that in the neoadjuvant docetaxel and gemcitabine arm the toxic effect with the greatest increase in frequency compared with the toxic effects of docetaxel alone was neutropenia in 34 % of the patients (NCI grade 3 and 4). Trials in the metastatic setting report increased rates of neutropenia (47.9 %) and thrombocytopenia (6.1 %) compared with our results.…”
mentioning
confidence: 82%
“…Neoadjuvant chemotherapy is defined as a treatment option where chemotherapy is introduced before local treatment, either surgery or radiotherapy (Bear, 1998). This was introduced by De Lena et al (1978) who administered adriablastin and vincristine in 110 women with advanced BC, achieving response rates of 70% partial.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%